Encrypted Wireless (En-Fi) - Azmi, Adif Asyraf (Journal of Computing Technologies and Creative Content, 2019)
Public Wi-Fi have been known for numerousopportunity for attackers to steal informationfrom user connected to it. User data will be leakif not protected while using public Wi-Fi. Otherthan that, the router itself isn’t protected whichmean other user can sniff out the adminusername and password thus gaining fullcontrol over the router. This project is designingto counteract that problem by using VPNservice to encrypted data throughout thenetwork and encrypting the router webinterface.